Dynamics of Impervious Surfaces and Vegetation in Core Urban Areas of Global Megacities - Lei Zhang; Jinzhou Yuan; Ming Zhang; Wenzhuo Liu; Qian Wang (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Although many studies have shown that the expansion of impervious surfaces such as artificial buildings and roads is accompanied by a decrease in urban vegetation, recent studies have also pointed out that urban greening measures can promote vegetation growth. The above studies mostly focus on administrative regions such as a certain city, urban agglomeration, river basin, country, etc., ignoring the differences between suburbs and core urban areas with concentrated populations. This article proposes a fractional impervious surface index to estimate impervious surfaces and combines it with population information to define core urban area boundaries of megacities. Then, Landsat data are used to analyze dynamics of impervious surfaces and vegetation in core urban areas of 12 megacities around the world from 2013 to 2022. The results indicate a gradual increase in impervious surfaces within the core urban areas of 12 megacities. Most megacities have shown a significant decline in the growth rate of impervious surfaces since 2017, and growth rates of all megacities have tended to stabilize after 2019. Across all megacities, lower fractional vegetation cover (FVC) levels account for a higher proportion of area, with a gradual decline toward higher FVC levels. Most megacities have different FVC trends in core urban areas and entire city. The proportions of very high FVC areas in core urban areas of 12 megacities have not changed much, with fluctuations basically not exceeding 5% . This study helps to understand the spatiotemporal dynamic changes of vegetation in core urban areas and provide reference data for sustainable urban development.